Drug Trafficking and Youth Mortality in Brazil: An Expression of Human Rights’ Violations (2018)
This paper aims to analyze the intersectional problematic that surrounds the violations of adolescents’ human rights that happen in Brazil nowadays. It focuses, more specifically, on the involvement of these youths with drug trafficking, and on the relations between their participation in crime and the rising mortality rates amidst young age groups. A large part of Brazil’s children and teenagers grow up in contexts of social vulnerability, lack of opportunities, difficult access to economical assets, and personal devaluation. This situation often pushes young individuals into involvement with drug trafficking or armed robbery, since crime represents, in their context, a possibility for economic and social ascendance. In parallel, the criminal policy adopted by the Brazilian State, synthesized in the expression “war on drugs” and manifested in the promulgation of Law 11.343/06, focuses on repressive police actions, and favors imprisonment, while doing nothing to attack the social causes of the problem. The result is the mass incarceration of young and economically disfavored individuals as well as, not infrequently, their deaths during police approaches, characterizing a situation where these adolescents are both perpetuators and victims of violence.